Estimation of stature from head circumference measurements in students of a tertiary care hospital - Patil, R. A.; Kacahre, R. V.; Pawar, V. G.; Dode, P. S. (International Journal of Research in Medical Sciences, 2022)
Background: The present study was undertaken to reconstruct stature in males and females by using head circumference as a parameter. Methods: There was paucity of students during the period of study due to unavailability of students owing to COVID restrictions on physical attendance to classes. Hence, sample size had to be curtailed to 251 students. Hence, the study was carried out on 251 medical students, 136 males, and 115 females in the department of forensic medicine and toxicology, Swami Ramanand Teerth Rural Government Medical College (SRTRGMCH), Ambajogai, Maharashtra, India. Measurements of head circumference and height were made directly on each subject. The data collected was subjected to statistical methods. The measured heights from the data for males, and females were regressed against the measured head circumference variables using linear regression analysis. Results: Highly significant correlation was found between height and head circumference. The equation relating stature to the head circumference was derived as stature, y=97.19+1.11 HC for females and y=88.77+1.45 HC for males. The above findings may hence provide reliable method of estimation of height from skeletal remains in the forensic setup. Conclusions: Head circumference can be used to estimate stature in Maharashtrian population using the regression equation with reasonable accuracy to estimate stature.